"Si quid sunt manes ..." - Aspekter af gammelromersk dødekult - Toftager, Hanne (Religionsvidenskabeligt Tidsskrift, 1987)
On the basis of archeological and literary material from the centuries around the beginning of the Christian era, the article delineates popular religious beliefs about death. The understanding of death is reflected in the ritual burial practice and in the equipment of the grave and its significance. The grave is understood as a sacred place, dedicated to the divine “manes” of the deceased. Family graves are used, graves that function, on the one hand, as the abode of the deceased who lives according to the laws of the hereafter, and, on the other, as a place of commemoration for the bereaved who come at fixed intervals to sacrifice. Further, the grave and the tombstone with the portrait of the deceased is seen as a symbolic substitute for the deceased thus causing the grave to signify that death has usurped the community of the living and at the same time that the deceased in his grave is part of another, transcendant community consisting of the living and the dead. The dual nature of the portrait on the tombstone reflects the dual nature of the cult of death: protective measures mirroring a deep-rooted anxiety alternate with expressions of veneration, thus marking that the deceased is radically different and at the same time familiar. This duality also characterizes some present-day Italian burial practices, as outlined in the closing paragraph.